Obtaining high purity silica from rice hulls - Silva Júnior,José da (2010)
Many routes for extracting silica from rice hulls are based on direct calcining. These methods, though, often produce silica contaminated with inorganic impurities. This work presents the study of a strategy for obtaining silica from rice hulls with a purity level adequate for applications in electronics. The technique is based on two leaching steps, using respectively aqua regia and Piranha solutions, which extract the organic matrix and inorganic impurities. The material was characterized by Fourier-transform infrared spectroscopy (FTIR), powder x-ray diffraction (XRD), x-ray fluorescence (XRF), scanning electron microscopy (SEM), particle size analysis by laser diffraction (LPSA) and thermal analysis.